Assembly of nascent DNA into nucleosome structures in simian virus 40 chromosomes by HeLa cell extract. - Sugasawa, K (1990)
A soluble system was developed that could support DNA replication in simian virus 40 (SV40) chromosomes. DNA synthesis in this system required the presence of purified SV40 large tumor antigen, SV40 chromosomes prepared from virus-infected monkey cells, a crude extract from HeLa cells, and several low-molecular-weight components. In comparison to the replication of purified SV40 form I DNA, the rate of DNA synthesis was 15 to 20% in this system. DNA synthesis started near the replication origin of SV40 and proceeded bidirectionally in a semiconservative manner. Micrococcal nuclease digestion experiments revealed that the replicated DNA produced in this system became organized into a regularly spaced array of nucleosome core particles when an appropriate amount of purified HeLa core histones was added to the reaction mixture. SV40 form I DNA replicating under the same conditions was also assembled into nucleosomes, which were arranged in a rather dispersed manner and formed an aberrant chromatin structure.